1992
DOI: 10.1111/j.1651-2227.1992.tb12322.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin‐induced IgG2 and IgG4 deficiencies in a patient with epilepsy

Abstract: A five-year-old girl with epilepsy and recurrent respiratory infections was investigated for serum IgG subclass concentrations. She was diagnosed as having a combined deficiency of IgG2 and IgG4 with a decreased serum concentration of IgA and IgG3 and was given replacement therapy with i.v. immunoglobulins. Since then, she has been free from respiratory infections. After phenytoin therapy was stopped, IgG subclass deficiency improved. This case describes the further action of phenytoin on the immune system, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
1
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
(1 reference statement)
0
7
1
1
Order By: Relevance
“…After the approval of the use of CBZ for the treatment of convulsive seizures in 1974, several studies have evaluated the repercussions of this medication on the immune system [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The alterations in cellular immunity have been extensively studied 3 , but the serum concentration and function of immunoglobulins still receives special attention in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After the approval of the use of CBZ for the treatment of convulsive seizures in 1974, several studies have evaluated the repercussions of this medication on the immune system [3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The alterations in cellular immunity have been extensively studied 3 , but the serum concentration and function of immunoglobulins still receives special attention in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the immunologic behavior of CBZ users reported no variations in IgG levels, but rather a decrease in serum IgA and IgM levels 3,[8][9][10][11] , with few reports of changes in IgG concentrations related to CBZ use [4][5][6][7] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease can be caused by tempo rary immaturity of the immune system. It has been observed after viral infection, during phenytoin medication [10], in pa tients with acute lymphoblastic leukemia receiving mainte nance treatment [11] and HIV séropositives [12]. IgG2 is es pecially important for the immune response against polysac charide antigens found in encapsulated bacteria [13],…”
Section: Discussionmentioning
confidence: 99%